A numerical analysis and experimental investigation of three oil grooves sleeve bearing performance. Issue 2 (11th March 2019) - Wang, Lili; Zeng, Qingliang; Lu, Changhou; Liang, Peng
Abstract : Purpose: This paper aims to reveal the cavitation characteristics of three oil wedges sleeve bearing and set the theoretical and experimental basis for defining the oil film boundary condition. Design/methodology/approach: Computational fluid dynamics model of three oil wedges sleeve bearings based on the Navier–Stokes equation is set using Fluent considering turbulent situation and two-phase flow theory. The cavitation characteristics of bearing is investigated by taking pictures of experiment. Findings: The rupture region of oil film and the contours of air volume fraction increase distinctly with the increase of rotating speed and the decrease of input pressure. The critical rotating speed of cavitation occurrence and oil film pressure increases with the increase of input pressure. The change trend of experiment cavitation with the rotating speed and input pressure is consistent with theoretical cavitation in general. Originality/value: The finite element model of three oil wedges sleeve bearings is established based on the Navier-Stokes calculation equation of the fluid, two-phase flow theory and turbulent model. Sleeve bearing is transparent, the pictures of cavitation can be easily taken by high-speed camera, the cavitation characteristics of bearing is studied by experiment. The cavitation performance of three oil wedges bearings is studied with the change of input pressure and rotating speed, the change trend is basically consistent for theory and experiment. The study on critical rotating speed of cavitation occurrence is benefit for defining the oil film boundary condition.